Comprehensive molecular profiling of pulmonary pleomorphic carcinoma - Masaaki Nagano (Nature Portfolio, 2021)
Abstract Information regarding the molecular features of pulmonary pleomorphic carcinoma (PPC) is insufficient. Here, we performed next-generation sequencing to determine the genomic and transcriptomic profiles of PPC. We sequenced the DNAs and RNAs of 78 specimens from 52 patients with PPC. We analyzed 15 PPC cases to identify intratumoral differences in gene alterations, tumor mutation burden (TMB), RNA expression, and PD-L1 expression between epithelial and sarcomatoid components. The genomic alterations of six cases of primary tumors and corresponding metastatic tumors were analyzed. KRAS mutations (27%) were the most common driver mutations, followed by EGFR (8%), and MET (8%) mutations. Epithelial and sarcomatoid components shared activating driver mutations, and there were no significant differences in CD274 expression or TMB between the two components. However, PD-L1 was highly expressed in the sarcomatoid component of several cases compared with the epithelial component. Primary and metastatic tumors shared oncogenic mutations among genes such as KRAS and TP53, and additional alterations including NOTCH4 mutations were specifically identified in the metastatic regions. Our data suggest that therapies targeting activating driver mutations may be effective for patients with PPC and that immune checkpoint inhibitors of PPC may be recommended after careful assessment of PD-L1 expression in each epithelial and sarcomatoid component.